Reader’s Digest: global learning through reading / Irma Ahmad ... [et al.]. - Ahmad, Irma; Wan Mustapha, Wan Zumusni; Yusof, Nurul Kamalia; Mohd Mokhtar, Norashikin; Abu Hasim, Aeimi Ruzanna (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Education serves as the foundation for the development of knowledge, skills, and human capital, which drives worldwide innovation and growth in the economy. All students deserve a high-quality global education. As the world grows more interconnected, the government sees the importance of global learning and the need to modernise its educational systems and prepare youth for success. To make this possible, educators play an important role in creating a globally inclusive environment for students. There is no doubt that our lives are becoming ever more global as barriers between nations and people begin to fade. Students should be exposed to the issues that transcend national boundaries. For example, educators across all fields can create meaningful learning experiences that delve into the viewpoints of other cultures, use international examples, and promote critical thinking about global issues. Together, these global learning experiences equip students to engage the larger world with greater confidence, thoughtfulness, and empathy.